Financial Statement Fraud Analysis Through Hexagon Fraud Theory Approach - Nurjanna, Nurjanna; Muchran, Muchriana; Sulisyanti, Rini (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2024)
Purpose – This study aims to analyze whether pressure or stimulus factors influence financial statement fraud, to analyze whether the capability factor influences financial statement fraud, to analyze whether collusion fachtors influence financial statement fraud, to analyze whether opportunity fachtors influence financial statement fraud, to analyze whether rationalization factors influence financial statement fraud, and to analyze whether the ego factor influences financial statement fraud. Design/methodology/approach – The analytical method used is quantitative analysis using the SPSS 21 statistical formula. Findings – The results of this research are stimulus factors, capability factors, collusion factors, opportunity factors, rationalization factors and ego factors has an influence on fradulent financial statements. Originality – Sources of data used in this study are secondary data obtained from the company’s published annual financial reports. Keywords: Fraud, Hexagon Approach, Financial Statement Paper Type Research Result